Motivating Factors That Taxpayer Does Not Make Tax Restitution on The Values Added Tax - Ni Putu Eka Widiastuti (The Indonesian Journal of Accounting Research, 2014)
Abstract: Restitution of value-added tax (VAT) is the difference between the value causes a procedure provided by the government to returning excess tax amount remitted by the taxpayer (Taxable Employers) added tax-in (VAT – in) and the value added tax-out (VAT – Out) where the amount is credited VAT-in is greater than VAT-out. This study uses primary data collected from respondents’ answers taxpayers through the questions asked by questionnaire. Data were analyzed using factor test, where the purpose of this study was to prove the factors that motivate taxpayers do not do refunds of the VAT. The results of this study indicate that four factors motivate taxpayers do not do refunds of the VAT. They are the 1st factor a period of restitution, the 2nd factor is tax audits, the 3rd factor is the restitution procedure, and 4 th factor is service tax officer.Abstrak: Restitusi pajak pertambahan nilai (VAT) adalah selisih antara nilai yang menyebabkan prosedur yang disediakan oleh pemerintah untuk mengembalikan kelebihan jumlah pajak yang dikirim oleh wajib pajak (Pengusaha Kena Pajak) menambahkan pajak (PPN - in) dan nilai tambah tax-out (PPN - Out) di mana jumlah dikreditkan PPN-in lebih besar dari VAT-out. Penelitian ini menggunakan data primer yang dikumpulkan dari jawaban responden wajib pajak melalui pertanyaan yang diajukan oleh kuesioner. Data dianalisis menggunakan uji faktor, di mana tujuan penelitian ini adalah untuk membuktikan faktor-faktor yang memotivasi wajib pajak tidak melakukan pengembalian uang dari PPN. Hasil penelitian ini menunjukkan bahwa empat faktor motivasi wajib pajak tidak melakukan pengembalian uang dari PPN. Mereka adalah faktor pertama periode restitusi, faktor kedua adalah audit pajak, faktor ke-3 adalah prosedur restitusi, dan faktor ke-4 adalah petugas pajak layanan.